2013
DOI: 10.1097/tp.0b013e3182a2b492
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Postoperative Atrial Fibrillation in Kidney Transplant Recipients

Abstract: AF is a notable complication of kidney, and particularly simultaneous liver/kidney, transplant surgery. Age, previous myocardial infarction, and simultaneous liver/kidney transplant independently predicted POAF. The modified CHA2DS2-VASc score could be useful to predict POAF risk in kidney transplant candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
1
28
1
Order By: Relevance
“…However, POAF occurring several years later may have different etiologies and risk profiles compared with those occurring in the immediate postoperative period. One study with 26 patients found the incidence of POAF was 20% after combined kidney and liver transplant (16). In our study, 88 patients had combined kidney and liver transplant.…”
Section: Discussionmentioning
confidence: 92%
“…However, POAF occurring several years later may have different etiologies and risk profiles compared with those occurring in the immediate postoperative period. One study with 26 patients found the incidence of POAF was 20% after combined kidney and liver transplant (16). In our study, 88 patients had combined kidney and liver transplant.…”
Section: Discussionmentioning
confidence: 92%
“…This hypothesis is amenable for intervention trials that would aim to establish and maintain sinus rhythm before and during the intraoperative transplantation phase. It has recently been reported that development of AF in the postoperative period after kidney transplantation can be predicted by recipient age, a history of myocardial infarction, and combined liver/kidney transplantation . The pathophysiological mechanisms that trigger postoperative AF remain unclear, but ischemia/reperfusion events, resulting in the formation of oxidative stress and a systemic inflammatory response, have been shown to cause structural modifications of myocardial tissue and atrial remodeling …”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that development of AF in the postoperative period after kidney transplantation can be predicted by recipient age, a history of myocardial infarction, and combined liver/kidney transplantation. 19 The pathophysiological mechanisms that trigger postoperative AF remain unclear, but ischemia/reperfusion events, resulting in the formation of oxidative stress and a systemic inflammatory response, have been shown to cause structural modifications of myocardial tissue and atrial remodeling. [20][21][22] The American Heart Association and the American College of Cardiology currently recommend betamimetic blockers for the prevention of postoperative AF in patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…47 Among 304 kidney transplant recipients at a single center in Italy, 6.9% had incident AF in the post-operative period after surgery (median time of 3 days). 48 The cumulative post-operative AF risk was highest on the day of surgery (2.5%), increased steeply up to day 3 (5.3%) and reached 9.5% on the 19 th day of admission. 48 The highest risk of incident AF after kidney transplant was among kidney transplant recipients who were older, men and white with a higher burden of hypertension and coronary heart disease.…”
Section: Af and Kidney Transplantmentioning
confidence: 87%
“…48 The cumulative post-operative AF risk was highest on the day of surgery (2.5%), increased steeply up to day 3 (5.3%) and reached 9.5% on the 19 th day of admission. 48 The highest risk of incident AF after kidney transplant was among kidney transplant recipients who were older, men and white with a higher burden of hypertension and coronary heart disease. Another analysis examined the prevalence of pre - transplant AF and associated outcomes after transplant among over 62,000 first kidney transplant recipients.…”
Section: Af and Kidney Transplantmentioning
confidence: 87%